HUBUNGAN PENGETAHUAN DENGAN SIKAP REMAJA TENTANG PENDIDIKAN SEKSUALITAS DI DESA LUBUK SIAM KABUPATEN KAMPAR: HUBUNGAN PENGETAHUAN DAN SIKAP REMAJA TENTANG PENDIDIKAN SEKSUALITAS DI DESA LUBUK SIAM KABUPATEN KAMPAR - Komaria Susanti; Chintya Kumala Sari (Institut Kesehatan dan Teknologi Al Insyirah, 2021)
Poor sexual behavior among adolescents is closely related to adolescent lack of knowledge about sexuality, one’s attitude is influenced by mass media, one of which is the internet, peer groups can function as a substitute for family because adolescents feel more accepted, understood, and become more familiar with peer groups. In adolescents the influence of the environment in determining behavior is very strong. The purpose of this study was to determine the relationship between knowledge and attitudes of adolescents about sexuality education In Lubuk Siam Village, Kampar District. The method used is the method of observation with a cross sectional approach. Total population of 109 respondents, and a sample of 109 respondents. The sampling technique uses total sampling. The research instrument was a questionnaire. When the research was carried out from september – march 2021. The statistical test in this study was the chi square test. From the results of the univarate analysis the number of male responden was 59 people, and 50 were female. 72 people lacking knowledge, enough 25 people, both 12 people, on a positive attitude 26 people, and negative 83 people. From the chi square test, it was found that there was a relationship between knowledge and attitudes towards sexuality education in adolescents. It is hoped that in the future the knowledge of adolescent about sexuality education can be further improved, and regular meetings are held, one of which is counseling about adolescents in lubuk siam village.